Edge shear flows and particle transport near the density limit of the HL-2A tokamak. (5th December 2017) - Hong, R.; Tynan, G.R.; Diamond, P.H.; Nie, L.; Guo, D.; Long, T.; Ke, R.; Wu, Y.; Yuan, B.; Xu, M.
Abstract: Edge shear flow and its effect on regulating turbulent transport have long been suspected to play an important role in plasmas operating near the Greenwald density limit n G . In this study, equilibrium profiles as well as the turbulent particle flux and Reynolds stress across the separatrix in the HL-2A tokamak are examined as n G is approached in ohmic L-mode discharges. As the normalized line-averaged density n ̄ e / n G is raised, the shearing rate of the mean poloidal flow ω s h drops, and the turbulent drive for the low-frequency zonal flow (the Reynolds power P R e ) collapses. Correspondingly, the turbulent particle transport increases drastically with increasing collision rates. The geodesic acoustic modes (GAMs) gain more energy from the ambient turbulence at higher densities, but have smaller shearing rate than low-frequency zonal flows. The increased density also introduces decreased adiabaticity which not only enhances the particle transport but is also related to reduction in the eddy-tilting and the Reynolds power. Both effects may lead to cooling of edge plasmas and therefore the onset of MHD instabilities that limit the plasma density.